2021
DOI: 10.3390/min11050498
|View full text |Cite
|
Sign up to set email alerts
|

The Response of the Soil Microbiome to Contamination with Cadmium, Cobalt and Nickel in Soil Sown with Brassica napus

Abstract: Soil fertility is determined by biological diversity at all levels of life, from genes to entire biocenoses. The aim of this study was to evaluate bacterial diversity in soil contaminated with Cd2+, Co2+ and Ni2+ and sown with Brassica napus. This is an important consideration because soil-dwelling microorganisms support phytoremediation and minimize the adverse effects of heavy metals on the environment. Microbial counts, the influence (IFHM) of Cd2+, Co2+ and Ni2+ on microorganisms, the colony development (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…In the presence of these hazardous heavy metals, enzymes may be inactivated, and cell function may be damaged due to metals forming chelation and precipitates with important metabolites [276]. Long-term and short-term pollution of heavy metals in soil leads to negative impact on microbial activity, particularly the microbial respiration and soil enzyme activity which results in a drop in microbial population [277,278]. It also resulted in reduction in genetic diversity in the population, relative to untreated or uncontaminated soils [276].…”
Section: Fertilizermentioning
confidence: 99%
“…In the presence of these hazardous heavy metals, enzymes may be inactivated, and cell function may be damaged due to metals forming chelation and precipitates with important metabolites [276]. Long-term and short-term pollution of heavy metals in soil leads to negative impact on microbial activity, particularly the microbial respiration and soil enzyme activity which results in a drop in microbial population [277,278]. It also resulted in reduction in genetic diversity in the population, relative to untreated or uncontaminated soils [276].…”
Section: Fertilizermentioning
confidence: 99%
“…Organotrophic bacteria were the most resistant to Co 2+ , whereas actinobacteria-to Cd 2+ . Our previous research [4] conducted with soil sown with Brassica napus demonstrated actinobacteria to be more resistant to the effects of Cd 2+ than Co 2+ and Ni 2+ . The diversified effects of heavy metals on microorganisms were also pinpointed by Zaborowska et al [69] and Giller et al [72].…”
Section: Sensitivity Of Soil Microorganisms To the Effects Of Ni 2+ ...mentioning
confidence: 95%
“…Microbiological diversity of the soil environment is essential because species abundance ensures ecological stability of ecosystems and adaptation to harsh environmental conditions [1,2]. The development of specialized microorganisms promotes plant growth and development in soils contaminated with, e.g., heavy metals [3,4]. The cooperation between rhizospheric microorganisms and plants is highly beneficial as it mitigates toxic effects of heavy metals in soil and controls their penetration into and accumulation in cells of microorganisms and plants [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The growth and development of crop plants are mainly correlated with the soil condition designated for their cultivation, and a reliable indicator of changes in the soil is its microbiome [27,28]. Microorganisms inhabiting the soil constitute a diverse group of organisms that is also involved in nutrient conversion and the detoxification of organic and inorganic pollutants [29][30][31]. They therefore contribute to maintaining the proper functioning and health of the soil [32].…”
Section: Introductionmentioning
confidence: 99%